2007
DOI: 10.1128/jvi.02291-06
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the Sendai Virus M Protein through a Novel Short Interfering RNA Approach Inhibits Viral Particle Production but Does Not Affect Viral RNA Synthesis

Abstract: Short RNA interference is more and more widely recognized as an effective method to specifically suppress viral functions in eukaryotic cells. Here, we used an experimental system that allows suppression of the Sendai virus (SeV) M protein by using a target sequence, derived from the green fluorescent protein gene, that was introduced in the 3 untranslated region of the M protein mRNA. Silencing of the M protein gene was eventually achieved by a small interfering RNA (siRNA) directed against this target sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 49 publications
2
44
1
Order By: Relevance
“…While the fusogenicity of NiVeG⌬M was slightly enhanced, replication kinetics was significantly impaired. Together with the release of large amounts of viral and cellular proteins and the severely reduced infectivity and stability, our data indicate that the M protein is essential for proper NiV particle assembly, consistent with its role in other paramyxoviruses (21,(31)(32)(33).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…While the fusogenicity of NiVeG⌬M was slightly enhanced, replication kinetics was significantly impaired. Together with the release of large amounts of viral and cellular proteins and the severely reduced infectivity and stability, our data indicate that the M protein is essential for proper NiV particle assembly, consistent with its role in other paramyxoviruses (21,(31)(32)(33).…”
Section: Discussionsupporting
confidence: 75%
“…While some attempts to generate members of the Paramyxoviridae family without complementation of functional M proteins were not successful (31)(32)(33), M protein-deleted measles (MV⌬M) and respiratory syncytial (M-null HRSV) viruses have been recovered (20,21). While M-null HRSV was completely defective in virus budding (21), limited amounts of infectious MV⌬M were found in the supernatant (20), indicating a varying importance of the M protein contribution among different genera.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be the result of the unique properties of closely related viruses. In the case of Sendai virus, another paramyxovirus, it was shown that VLPs were not or were poorly generated when M expression was suppressed (40). While our data show that the production of infectious HRSV progeny was nearly abrogated in the absence of M, we cannot exclude the possibility that noninfectious VLPs were released.…”
Section: Discussioncontrasting
confidence: 58%
“…An important role for M in virion production was anticipated based on a previously reported HRSV minireplicon system (58) and analogy to the roles of M proteins from other paramyxoviruses (12,29,40,46). The growth analysis shown in Fig.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation